2014
DOI: 10.1253/circj.cj-13-1234
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Right Atrial Pressure on Inferior Vena Cava Ultrasound in Asian Patients

Abstract: Background: Right atrial pressure (RAP) is commonly estimated using inferior vena cava (IVC) diameter and its respirophasic variations. Although a guideline has been provided for estimation of RAP due to variation in IVC dimensions based on studies in Western subjects, echocardiographic values in Asian subjects are unknown. Methods and Results:We studied 369 patients who underwent IVC ultrasound within 24 h of right heart catheterization (RHC). The maximum and minimum IVC diameter during a respiratory cycle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Although catheterization was performed within 24 h of IVC ultrasound, interpretation of the IVC parameters for RAP was limited. 12 Furthermore, a previous study, 8 as well as our study, 12 included patients with heart transplantation, and increased stiffness of the IVC at the join between the donor and recipient might have affected the IVC values or their respiratory variation. 13 In the present study, we compared the invasive RAP value with IVC parameters that were obtained simultaneously and analyzed the optimal IVC parameter cut-off values to predict elevated RAP in a relatively large East Asian cohort.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Although catheterization was performed within 24 h of IVC ultrasound, interpretation of the IVC parameters for RAP was limited. 12 Furthermore, a previous study, 8 as well as our study, 12 included patients with heart transplantation, and increased stiffness of the IVC at the join between the donor and recipient might have affected the IVC values or their respiratory variation. 13 In the present study, we compared the invasive RAP value with IVC parameters that were obtained simultaneously and analyzed the optimal IVC parameter cut-off values to predict elevated RAP in a relatively large East Asian cohort.…”
mentioning
confidence: 74%
“…From our ROC curve, a cut-off value of 21 mm had a sensitivity of 50% and specificity of 97% (Figure 3), and this sensitivity was very low, as we had previously published. 12 A new classification scheme may be required based on these results. However, it must be recognized that our population was East Asian, because we encounter mainly East Asian patients in our daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 33 reported that the IVC parameters used to detect elevated RAP were significantly smaller in their cohort of 369 Asian patients, compared to a previously reported Western cohort. This is likely due to the generally smaller Asian physique.…”
Section: Ethnicity Of Patientsmentioning
confidence: 74%
“…An IVC max diameter 1.9 cm was found to be the optimal cutoff to predict an elevated right atrial pressure >10 mm Hg in a study of Japanese cardiac patients with a relatively lower body mass index. 39 Another limitation is the timing of the admission IVC measurement within the first 24 hours of arrival to the hospital rather than immediately upon arrival to the emergency department. We were not able to control for interventions given in the emergency department prior to the measurement of the admission IVC, including doses of diuretics.…”
Section: Figmentioning
confidence: 99%